(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article Batrak S.A., Kovalskaya O.V. analyzes some theoretical and pedagogical principles of forming students’ concepts in lessons on subjects of artistic and aesthetic cycle (grades 5-11), the possibility of using etymologization to increase interest in the process of learning them knowledge.